How financial incentives induce disability insurance recipients to return to work - Andreas Ravndal Kostøl; Magne Mogstad (Institute for the Study of Labor (IZA), 2012)
Disability Insurance (DI) programs have long been criticized by economists for apparent work disincentives. Some countries have recently modified their programs such that DI recipients are allowed to keep some of their benefits if they return to work, and other countries are considering similar return-to-work policies. However, there is little empirical evidence of the effectiveness of programs that incentivize the return to work by DI recipients. Using a local randomized experiment that arises from a sharp discontinuity in DI policy in Norway, we provide transparent and credible identification of how financial incentives induce DI recipients to return to work. We find that many DI recipients have considerable capacity to work that can be effectively induced by providing financial work incentives. We also show that providing work incentives to DI recipients may both increase their disposable income and reduce program costs. Our findings also suggest that targeted policies may be the most effective in encouraging DI recipients to return to work.
Keywords: H53; H55; I18; J21; 330; disability insurance; financial incentives; labor supply; regression discontinuity design; Erwerbsunfähigkeitsrente; Arbeitsangebot; Ökonomischer Anreiz; Berufliche Integration; Test; Norwegen